Near infrared quantitative chemical imaging as an objective, analytical tool for optimization of the industrial processing of wheat - Boatwright, Mark Daniel (Kansas State University, 2018)
The technique of near infrared chemical imaging has been widely used for many industrial applications. It offers selectivity and/or sensitivity for numerous organic functional groups. The advantage of the near infrared spectroscopic region is the linear relationship of absorbance and concentration that enables quantitation. This universally employed technique has been a boon for research studies in the industrial process of wheat milling for the production of flour. The milling process has numerous sequential grinding and sieving steps that enable selective physical segregation of a starch rich endosperm product from wheat. Thousands of spectra of purified endosperm and non-endosperm standards are collected to develop a spectral library. Quantitation of the purity of individual processing streams is accomplished by applying a partial least squares calibration that is based upon the spectral library. The quantitative chemical imaging technique is useful for determination of endosperm purity profiles for mill flour streams. These plots reveal purity changes as less pure streams are added to produce a flour blend. The chemical structural basis furthermore allows comparison of purity even with changes in the wheat blend being milled with representative standardization. Furthermore, whereas a certain section of sieves is responsible, for designating the material defined as flour, application of the spectroscopic method is obvious. Select examples of key processing streams were studied to show the possibility of sieve-by-sieve analysis of the physical separation to provide mill optimization. These novel methods of analysis would not be possible without the sensitive and selective method of quantitative chemical imaging. Application of this technique to a few select unit processes is projected to reasonably affect a 1% increase in the yield of high quality flour. This amounts to a significant financial gain against low profit margins.
Keywords: Spectroscopic imaging; Wheat milling; Optimization